(untitled) (LEARNing Landscapes, 2011)
This article is a self-study of the experience of introducing sock knitting as a course assignment for teacher candidates. The idea originated from a personal desire to easily turn a sock heel while dealing with dementia in an aging parent who once knit well. The adaptations this assignment have undergone are explained with regards to a personal ongoing study of brain research, reflections about teaching knitting, and students’ comments about the challenges of learning to knit socks.